2016
DOI: 10.1093/jat/bkw018
|View full text |Cite
|
Sign up to set email alerts
|

3-Methylmethcathinone—Interpretation of Blood Concentrations Based on Analysis of 95 Cases

Abstract: 3-Methylmethcathinone (3-MMC) has been one of the most popular new psychoactive substances (NPS) in Poland in recent years. 3-MMC was found in blood in 95 cases sent to the Institute of Forensic Research (IFR) during the two and a half year period, from 2013 to half of 2015. 3-MMC was determined in 13 and 48 cases in 2013 and 2014 year-round casework, respectively, while only in the first half of 2015 year it was present in 34 cases. In most cases, 3-MMC was detected together with other novel psychoactive subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Unclear, however, is the extent to which these mechanisms contribute to clinical adverse effects of cathinones relative to sympathomimetic toxicity. Numerous cathinone-related fatalities have been reported (Adamowicz et al 2014(Adamowicz et al , 2016Bäckberg et al 2015c;Barrios et al 2016;Beck et al 2016 Analytically confirmed cases of cathinone-related deaths were mainly attributed to hyperthermia, hypertension, cardiac arrest, and serotonin syndrome Zaami et al 2018).…”
Section: Adverse Effects Of Cathinone and Pyrovalerone Derivativesmentioning
confidence: 99%
“…Unclear, however, is the extent to which these mechanisms contribute to clinical adverse effects of cathinones relative to sympathomimetic toxicity. Numerous cathinone-related fatalities have been reported (Adamowicz et al 2014(Adamowicz et al , 2016Bäckberg et al 2015c;Barrios et al 2016;Beck et al 2016 Analytically confirmed cases of cathinone-related deaths were mainly attributed to hyperthermia, hypertension, cardiac arrest, and serotonin syndrome Zaami et al 2018).…”
Section: Adverse Effects Of Cathinone and Pyrovalerone Derivativesmentioning
confidence: 99%
“…The details of the derivatization process for all the analyzed compounds are presented in Table 1. LLE was chosen as the extraction technique because of its many advantages, including its simplicity and minimal time requirements, which make it ideal for routine forensic toxicology analyses. Various organic solvents, including ethyl acetate [19], 1-chlorobutane [26], and mixtures of ethyl acetate with hexane [27] have been proposed in the literature for the extraction of ATSs and cathinones from biological samples. In our study, ethyl acetate and 1-chlorobutane were tested, and higher recoveries and lower influence from the matrix (occurrence of additional peaks in the chromatogram as interferences in RTs of analytes) were obtained when using ethyl acetate (Fig.…”
Section: Extraction and Derivatizationmentioning
confidence: 99%
“…The pKa values of most of the compounds of interest are higher than 9; therefore, alkalization of the sample before extraction is required. Typically, the addition of carbonate buffer (pH 12) [26] is suggested for this purpose. However, in that study, LC-MS/MS was utilized as the detection technique, and we found that when using GC-MS/MS and derivatization with PFPA, a carbonate buffer led to the extraction of many Table 1) impurities from the blood samples.…”
Section: Extraction and Derivatizationmentioning
confidence: 99%
“…3,4-DMMC has recently been sold and confiscated in various countries (Locos and Reynolds, 2012;Odoardi et al, 2016;Zancajo et al, 2014). 3-Methylmethcathinone (3-MMC) has become one of the most popular NPS in various European countries after the ban of mephedrone, and it has been associated with clinical toxicity and several fatal cases (Adamowicz et al, 2016;Adamowicz et al, 2014;Backberg et al, 2015;European Monitoring Centre for Drugs and Drug Addiction, 2015). 5-(2-Aminopropyl)indole (5-IT) is an indole derivative and stimulant NPS that has been associated with numerous fatal and non-fatal intoxications in recent years (Backberg et al, 2014;Katselou et al, 2015;Kronstrand et al, 2013;Seetohul and Pounder, 2013).…”
Section: Introductionmentioning
confidence: 99%